Optimasi Aktivasi Arang Aktif dari Arang Hidro Tempurung Buah Kelapa Sawit Menggunakan Metodologi Permukaan Respon (Optimization of Activated Carbon from Oil Palm Shell Hydrochar Using Response Surface Methodology) - Ismail Budiman; Dede Hermawan; Fauzi Febrianto; Subyakto Subyakto; Gustan Pari (Masyarakat Peneliti Kayu Indonesia, 2019)
In this study, activated carbon was prepared using hydrochar derived from oil palm shell through hydrothermal carbonization (HTC), and activated by 5% kalium hydroxide (KOH). The activation process was carried out using a temperature of 700 °C - 800 °C, with activation time of 60-120 minutes. The parameters of the activation process were optimised by response surface methodology (RSM). The central composite design (CCD) is used to determine the effect of activation temperature and activation time on some responses i.e. proximate analysis, ultimate analysis, methylene blue number, iodine number, electrical conductivity, yield percentage, and some gas pollutants adsorption. The results showed that almost all of activated charcoal met the technical standard of activated charcoal of SNI 06-3730-1995 for moisture content, ash content, volatile matter, fixed carbon, iodine number, and methylene blue number. The optimum conditions for the activation process involving the response observed were at 787.85 °C for 116.52 minutes